Study of the Beam-Wave Interaction Behavior of the Side-Coupled Cavity Structure - Tripathi P.; Kumar A.; Dwivedi S.; Jain P.K. (My University, 2025)
In this article, RF wave and electron beam interaction behavior of the side-coupled cavity (SCC) structure, operating in the transverse magnetic (TM) mode has been investigated using the field matching technique. For the analysis, Vlasov-Maxwell's equations have been used to describe the EM fields in the beam present region of the SCC structure. All the harmonics present in the structure have been considered for the analysis of the dispersion characteristics and growth rate of the SCC structure. The temporal growth rate behavior with respect to the different beam parameters has also been explored. To validate the developed analysis, computed dispersion values have been compared with those of the simulated, for the special case (i.e., r\text {e}} =0 ). Furthermore, the analytically temporal growth rate has also been compared with the simulated values. The obtained computational and simulated values have been found in agreement within ±5%. © 1973-2012 IEEE.